2020
DOI: 10.1371/journal.pone.0229588
|View full text |Cite
|
Sign up to set email alerts
|

Orchard recycling improves climate change adaptation and mitigation potential of almond production systems

Abstract: There is an urgent need to develop climate smart agroecosystems capable of mitigating climate change and adapting to its effects. In California, high commodity prices and increased frequency of drought have encouraged orchard turnover, providing an opportunity to recycle tree biomass in situ prior to replanting an orchard. Whole orchard recycling (WOR) has potential as a carbon (C) negative cultural practice to build soil C storage, soil health, and orchard productivity. We tested the potential of this practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…OMA use has been shown to reduce tree water stress and increase soil water‐holding capacity. (Jahanzad et al, 2020; Lepsch et al, 2019; Walsh et al, 1996). In contrast, in a study comparing irrigated and non‐irrigated crops, manure did not alter the water‐holding capacity of three different soils (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…OMA use has been shown to reduce tree water stress and increase soil water‐holding capacity. (Jahanzad et al, 2020; Lepsch et al, 2019; Walsh et al, 1996). In contrast, in a study comparing irrigated and non‐irrigated crops, manure did not alter the water‐holding capacity of three different soils (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely attributed to an increase in microbial biomass C, associated with the substantial input of orchard biomass, and the stoichiometric necessity of assimilating additional N to balance the C/N ratio requirements of biomolecule synthesis. This is supported by a well-documented positive correlation between soil microbial biomass C and MBN across studies (Geisseler et al, 2010;Jahanzad et al, 2020). Thus, the increase in sustained soil microbial growth of the +biomass treatment and immobilization potential is likely associated with the additional energy and nutrients of incorporated orchard biomass within the topsoil (Bonanomi et al, 2011;Throckmorton et al, 2012).…”
Section: Whole-orchard Recycling Increases N Immobilization Without R...mentioning
confidence: 73%
“…At the main plot level, two biomass management treatments were established: a whole-orchard recycling treatment (+biomass), where the woody biomass was incorporated within the top 15 cm of soil in the tree row prior to planting by using land clearing equipment (Ironwolf 700B Slasher), which produced variable sizes of woody biomass ranging from ∼5 to 30 cm and a control treatment (−biomass), where trees were uprooted, burnt, and ashes reincorporated to the surface soil. Details of the trial design, establishment, and management can be found in Jahanzad et al (2020). At the short-term experiment (Lincoln), soil treatments were established in 2017 after termination of a 20-yr-old Westerner plum (Prunus salicina Lind) orchard in a complete randomized design with four replications.…”
Section: Site Description and Experimental Designmentioning
confidence: 99%
“…Adaptation and mitigation are the crucial factors to address the response to CC (Jahanzad et al 2020 ). Researchers define mitigation on climate changes, and on the other hand, adaptation directly impacts climate changes like floods.…”
Section: Mitigation and Adaptation Strategies Of Climate Changesmentioning
confidence: 99%
“…Researchers define mitigation on climate changes, and on the other hand, adaptation directly impacts climate changes like floods. To some extent, mitigation reduces or moderates greenhouse gas emission, and it becomes a critical issue both economically and environmentally (Botzen et al 2021 ; Jahanzad et al 2020 ; Kongsager 2018 ; Smit et al 2000 ; Vale et al 2021 ; Usman et al 2021 ; Verheyen 2005 ).…”
Section: Mitigation and Adaptation Strategies Of Climate Changesmentioning
confidence: 99%